Il sogno di Europa e il ratto di Zeus (Materiali di Estetica. Terza serie, 2020)
The aim of this paper is to give an account of the origin of the name “Europe” given to the continent and to narrate the myth of the girl so called abducted by Zeus. The myth of Europe that sees the derivation of the European population from the Phoenician people is close to that of Cadmus, Europe’s brother. The whole story makes continuous references to links between Phoenicia, Crete, and Boeotia, to the exchanges between Asia and Europe and to the intermingling of populations.
Keywords: Europe; Mith; Dream; Traditions